Visibilidad del archivero en el mundo laboral: reflejos de Brasil - Souza, Katia Isabelli Melo de (Revista Ibero-Americana de Ciência da Informação, 2011)
Investigating the visibility of archivists implies analyzing the employment’s landscape. In our analysis we considered the behavior of three key variables, training, professional groups and the labor market, in relation to the archivists with formal training. In this way, the research addressed the following aspects: as the archivist sees training, as an archivist sees the professional groups and as an archivist sees the profession. The results suggest new directions to the graduates and the practice archive has extrapolated the limits of the Law n º 6,546 of 1978, which regulates the profession, considering that the archivist has been creating new workspaces and adapting themselves to the research’s environment.